A Predictive Strategy Based on Volatile Profile and Chemometric Analysis for Traceability and Authenticity of Sugarcane Honey on the Global Market - Pedro Silva; Jorge Freitas; Fernando M. Nunes; José S. Câmara (Foods, 2021)
Sugarcane honey (SCH) is a syrup produced on Madeira Island and recognized by its unique aroma, a complex attribute of quality with an important influence on the final consumer’s acceptance of the product, and determined by a complex mixture of a large number of volatile organic compounds (VOCs) generated during its traditional making process and storage. Therefore, the purpose of this study was to establish the volatile profile of genuine SCH produced by a regional certified producer for seven years and compare it with syrups from non-certified regional producers and with producers from different geographical regions (Spain, Egypt, Brazil and Australia), as a powerful strategy to define the volatomic fingerprint of SCH. Different volatile profiles were recognized for all samples, with 166 VOCs being identified belonging to different chemical classes, including furans, ketones, carboxylic acids, aldehydes and alcohols. Chemometric analysis allowed (i) the differentiation between all syrups, being more pronounced between SCH and other syrups; and (ii) the identification of 32 VOCs as potential markers for the traceability and authenticity of SCH on the global market.